(untitled) (Economics and region, 2018)
The article deals with the features of the formation of energy security in Ukraine and the functions of business in its software were investigated. The role of energy service business and the role of government in the development of energy service companies which is a part of energy security was prescribe. The peculiarities of energy service business in the country were determined in the article. The main problem of energy service companies and mechanisms of i their activities intensification was determined.